Agripreneurs' Level Of Readiness For Environmentally-Friendly Mushroom Cultivation Waste Management - Rosmiza M. Z.; Rosniza Aznie Che Rose; Harifah Mohd Noor; Jabil Mapjabil; Mazdi Marzuki; Christina Andin @ Nur Qistina (AESS Publications, 2020)
Mushrooms are considered as an environmentally-friendly crops by using agricultural waste as substrate, while spent mushroom substrate (SMS) is reusable. However, mushroom cultivation waste (MCW) to be managed in environmentally-friendly is not much practiced by agripreneurs that led impact to the environment. Therefore, this study attempts to evaluate the level of agripreneurs' readiness on environmentallyfriendly management in post-harvest stage. It also evaluated the method of obtaining information regarding MCW management. Survey and interview were conducted involving 40 agripreneurs who were participants of the Young Mushroom Agripreneur Project Package Course. The results showed that agripreneurs knew and aware of caring the environmental quality when dealing with MCW, but most of them did not manage in a proper way, despite received advices from agency. Expanding agripreneurs awareness, skills capabilities in post-harvest techniques, and building-up networking with agencies and small-scale entrepreneur could essential strategies to manage MCW. This potentially increased agripreneurs’ income by reducing the input cost, generating side income and improve the environment.